Paradoxical dopaminergic drug effects in extraversion: dose- and time-dependent effects of sulpiride on EEG theta activity - Chavanon, Mira-Lynn; Wacker, Jan; Stemmler, Gerhard (Frontiers in Human Neuroscience, 2013)
Dopaminergic drugs frequently produce paradoxical effects depending on baseline performance levels, genotype or personality traits. The present study for the first time aimed to specify the mechanisms underlying such opposite effects using the following recently reported scenario as an example: Depending on the personality trait agentic extraversion (aE; i.e. assertiveness, dominance, ambition, positive emotionality) the selective dopamine D2 receptor antagonist sulpiride (200 mg) had opposite effects on resting posterior versus anterior theta activity in the electroencephalogram (EEG). In order to better describe these opposite pharmaco-EEG effects and to generate hypotheses regarding the underlying mechanisms, we measured the EEG intermittently over five hours in 80 healthy male volunteers extremely high or low in aE who had received either placebo or one of three doses of sulpiride (50 mg, 200 mg, or 400 mg). The findings suggest a model postulating stronger pre- versus postsynaptic subreceptor effects in high aE individuals compared to low aE individuals. Future studies may now systematically apply the model to other examples of paradoxical dopaminergic drug effects and examine the molecular basis of individual differences in pre- versus postsynaptic dopamine D2 subreceptor sensitivities and densities.